Peran Pengetahuan Halal, Religiusitas, dan Sikap terhadap Niat Beli Kosmetik Lokal Berlabel Halal - Kodriyah Zumrotun Nisa; Ahmad Ajib Ridlwan (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study examines the direct and indirect effects of halal knowledge, religiosity, and attitudes toward local cosmetic brand purchase intentions by millennial Muslim women. The research method used is Partial Least Square (PLS) Structural Equation Modeling (SEM) by testing the outer and inner models using SmartPLS 4.0 software. The sampling technique is purposive sampling. The respondents are 120 samples of millennial Muslim women in Indonesia. These results indicate that knowledge significantly directly or indirectly affects purchase intention through attitude. Religiosity has no significant direct effect on purchase intention. But through attitude, religiosity has a significant impact on purchase intention. Companies must provide more precise and detailed information regarding halal issues so that consumers understand the product they seek.